Interaction of hydroxychloroquine with SARS-CoV2 functional proteins using all-atoms non-equilibrium alchemical simulations. Issue 62 (7th July 2020) - Procacci, Piero; Macchiagodena, Marina; Pagliai, Marco; Guarnieri, Guido; Iannone, Francesco
Abstract : Using a combination of enhanced sampling molecular dynamics techniques and non-equilibrium alchemical transformations, we have shown that hydroxychloroquine may act as a mild inhibitor of important functional proteins for SARS-CoV2 replication. Abstract : Using a combination of enhanced sampling molecular dynamics techniques and non-equilibrium alchemical transformations with full atomistic details, we have shown that hydroxychloroquine (HCQ) may act as a mild inhibitor of important functional proteins for SARS-CoV2 replication, with potency increasing in the series PL pro, 3CL pro, RdRp. By analyzing the bound state configurations, we were able to improve the potency for the 3CL pro target, designing a novel HCQ-inspired compound, named PMP329, with predicted nanomolar activity. If confirmed in vitro, our results provide a molecular rationale for the use of HCQ or of strictly related derivatives in the treatment of Covid-19.